Energy Flexibility through the Integrated Energy Supply System in Buildings: A Case Study in Sweden. (July 2018) - Zhang, Yang; Campana, Pietro Elia; Yang, Ying; Lundblad, Anders; Yan, Jinyue
Abstract: The increasing penetration level of renewable energies requires more flexibility measures at the consumption side. Flexible energy prices have been placed by energy providers to promote flexibility measures from energy users. However, because of the current energy supply system in buildings, these flexible energy prices haven't been fully taken advantage of. This study focuses on the integrated energy supply system in buildings. A Swedish office building is used as the case study. The integrated energy supply system is built by installing new components, including battery, heat pump and electrical heater, and hot water tank. Mixed Integer Linear Programming (MILP) problems are solved to determine the optimal component capacities and operation profiles. The results indicate that all the studied system configurations achieve lower net present cost (NPC) than the current system. It suggests that the integrated energy supply system can take advantage of the flexible energy prices and lower the overall energy cost in the building. Among the studied configurations, the combination of air source heat pump (ASHP) and electrical heater (EH) has the lowest investment cost. This combination also has the lowest NPC except in the scenario with low borehole cost.